2018
DOI: 10.12968/bjon.2018.27.7.389
|View full text |Cite
|
Sign up to set email alerts
|

Transforming classroom questioning using emerging technology

Abstract: Classroom questioning is a common teaching and learning strategy in postgraduate nurse education. Technologies such as audience response systems (ARS) may offer advantage over traditional approaches to classroom questioning. However, despite being available since the 1960s, ARSs are still considered novel in many postgraduate nurse education classroom settings. This article aims to explicate the attitudes of postgraduate nursing students in an Irish academic teaching hospital towards classroom questioning (CQ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Because students can respond anonymously to open-ended questions and results of multiple-choice polls or quizzes are presented in aggregate, using Quizizz in the classroom may create increased psychological safety (e.g., Edmondson & Daley, 2020; Mahon et al, 2018), encouraging student participation. Responses can then be a jumping off for further discussion.…”
Section: Resource Descriptionmentioning
confidence: 99%
“…Because students can respond anonymously to open-ended questions and results of multiple-choice polls or quizzes are presented in aggregate, using Quizizz in the classroom may create increased psychological safety (e.g., Edmondson & Daley, 2020; Mahon et al, 2018), encouraging student participation. Responses can then be a jumping off for further discussion.…”
Section: Resource Descriptionmentioning
confidence: 99%
“…Digital gamification platforms engage students with many different learning styles due to their easy accessibility and ability to integrate well with varied teaching methods, while significantly increasing student participation and engagement in the classroom in comparison to traditional lecture‐based teaching 7–11 . Some research studies have suggested that the joy and excitement associated with playing educational games may result in improved student learning, engagement, and significantly higher course satisfaction 12–15 …”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Some research studies have suggested that the joy and excitement associated with playing educational games may result in improved student learning, engagement, and significantly higher course satisfaction. [12][13][14][15] Gamification learning has also been found to be an effective tool in higher education and postgraduate settings. [16][17][18][19] In the United States, dental education traditionally consists of didactic courses, as well as preclinical laboratory training work and clinical patient experiences.…”
Section: Introductionmentioning
confidence: 99%
“…1). Historically, in-class instant evaluation mainly involved teachers' evaluation and feedback to some or even a few students through classroom questioning and observation (Mahon et al, 2018). It was low in efficiency and difficult to use to achieve full coverage of evaluation, resulting in low fairness, objectivity, and universality of evaluation.…”
Section: Introductionmentioning
confidence: 99%